Gastric emptying of enterally administered liquid meal in conscious rats and during sustained anesthesia - Qualls-Creekmore, Emily (2009)
Gastric motility studies are frequently conducted with anesthetized animal models. Some studies on the same animal species have reported differences in vagal control of the stomach that could not be explained solely by slightly different experimental conditions. A possible limitation in the comparison between similar studies relates to the use of different anesthetic agents. Furthermore, anesthetic effects may also limit generalizations between mechanistic studies of gastric motility and the gastric motility of conscious animals. In the present study, we used the [(13)C]-breath test following a liquid mixed-nutrient test meal (Ensure®, 1 ml) with the aim to investigate the rate of gastric emptying in animals that were either conscious or anesthetized with either Inactin® or urethane. One week after determining the maximum (13)CO(2) concentration, time to peak [(13)C] recovery and gastric half emptying time in control, conscious rats, we repeated the experiment in the same rats anesthetized with Inactin® or urethane. Our data show that Inactin® anesthesia prolonged the time to peak [(13)C] recovery but did not significantly reduce the maximum (13)CO(2) concentration nor delay gastric half emptying time. Conversely, urethane anesthesia resulted in a significant slowing of all parameters of gastric emptying as measured by the maximum (13)CO(2) concentration, time to peak [(13)C] recovery and half emptying time. Our data indicate that Inactin® anesthesia does not significantly affect gastric emptying while urethane anesthesia profoundly impairs gastric emptying. We suggest that Inactin®, not urethane, is the more suitable anesthetic for gastrointestinal research.